Interrelation of indicators of management-plant health-conservation of forage resources in Cuban silvopastoral systems - Alonso, Osmel; Lezcano, J. C.; Sanabria, Yohania; Suris, Moraima (Cuban Journal of Agricultural Science, 2016)
In order to know how some management indicators of silvopastoral systems and their plant health contribute to the duration of the main forage species that form their associations, eight silvopastoral systems were sampled (six in Matanzas province and two in Mayabeque province). The botanical composition of grasslands was measured, as well as the amount of weeds, the associated entomofauna and its functional composition. Results indicated that, having a proper management in paddocks of silvopastoral systems, in paddocks 1, 2, 4, 6 and that of double purpose (bull fattening-seed production), there was an increase of the percentage of meadow species in the botanical composition and the density of leucaena trees per hectare was maintained. A similar performance was obtained with the presence of phytophagous and beneficial insects, mainly in these last, which prevented massive outbreaks of pests during the evaluated period. In the paddocks with SSP-4, 5, 6 and 7, where the percentage of natural grasse s increased, there was also an increase of the number of weeds, which is an indicator of bad management in animal husbandry, although in some cases they can be used as shelter and/or food (pollen or nectar) for predators and parasitoids, as it happened in the SSP-4 and 6. It can be concluded that management indicators (necessary rest time of the grass, animal stay and proning labors), as well as the conservation of natural enemies in the favorable environment created for them, allowed to maintain the biological balance (without massive outbreaks of pests) in the areas during the evaluated period. They also contributed to the persistence in time of the permanent forage plant resources that compose these systems (in their majority), and to their economic and environmental sustainability.Key words: management, plant resources conservation, plant health, silvopastoral systems